Hak Perempuan atas Kepemimpinan di Indonesia: Studi Komparasi Tata Negara dan Hukum Islam (POLITEA, 2023)
Indonesia is a country with a fairly high level of Islamic culture in its implementation. Islam itself is a religion that tends to place certain restrictions on women compared to men, but in reality many Muslim women become leaders in Indonesia. So how does Islamic law actually view this condition. The research aims to find out how the concepts of state and Islam relate to women's leadership. To find out the scale of success of women's leadership in Indonesia. This research method uses normative juridical. The results of this research are that based on the history of the Abi Bakrah hadith, it is clear that women are not permitted to occupy public leadership. Meanwhile, according to the state, the Election Law does not require a certain gender to lead. In addition, based on the scale of findings in this research, several regions in Indonesia that are led by women show community acceptance which is supported by a relatively high level of community satisfaction and are able to resolve problems that exist in society with a more humanistic approach compared to some areas led by men.